2020
DOI: 10.1556/2006.2020.00058
|View full text |Cite
|
Sign up to set email alerts
|

Identifying individuals in need of help for their uncontrolled gaming: A narrative review of concerns and comments regarding gaming disorder diagnostic criteria

Abstract: ObjectiveIn 2013, the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) included the diagnostic criteria of Internet gaming disorder (IGD). Then, in 2019, the 11th Revision of the International Classification of Diseases (ICD-11) categorized gaming disorder (GD) as an addictive disorder. This review aimed to review the raised concerns, debate, and research of IGD or GD criteria and provide suggestions to resolve them.MethodsA narrative review was conducted, and PubMed was searched fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 134 publications
(171 reference statements)
0
6
0
Order By: Relevance
“…Several studies have shown that excessive gaming tends to be relatively transient. 58,59 However, other studies have reported relatively long-term (6 months or 2 years) symptom stability. 60,61 In addition, given the sequential changes in children's problematic…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that excessive gaming tends to be relatively transient. 58,59 However, other studies have reported relatively long-term (6 months or 2 years) symptom stability. 60,61 In addition, given the sequential changes in children's problematic…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the overpathologization of gaming disorder may exacerbate moral panic about gaming 13–15 and hinder the development of effective, evidence‐based social interventions 10 . These remarks point to the need for further empirical studies on dysfunction, course, and prognosis, as well as the stability and predictability of the criteria to verify the validity and usefulness of the diagnostic criteria for IGD/gaming disorder 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Muller et al (60), the parameters for the three regression models should be estimated to test the moderated mediation hypothesis. This study specifically estimated the moderating effect of alienation on (1) the relationship between in-game social interaction and gaming disorder (model 1), (2) the relationship between in-game social interaction and online social capital (model 2), and (3) the relationship between online social capital and gaming disorder as well as the residual effect of in-game social interaction on gaming disorder (model 3). The specifications of the three models can be seen in Table 3.…”
Section: Testing For Moderated Mediationmentioning
confidence: 99%
“…Playing online games has become a highly prevalent activity, which, in some cases, engenders negative consequences, and becomes addictive (1,2). The 11th edition of the International Classification of Diseases [ICD-11; (3)] recently includes "gaming disorder, predominantly online" as an official diagnosis, and the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders [DSM-5; (4)] also includes online gaming disorder as an emerging mental health issue that should be further investigated.…”
Section: Introductionmentioning
confidence: 99%